Evaluation of the detectability of the integrin alpha-2 (platelet platelet glycoprotein Ia/IIa ) (ITGA2) gene polymorphism in pregnant women with fetal growth restriction syndrome - Aslonova Makhliyo Juraboyevna (Global Scientific Publishing, 2022)
The article presents a molecular genetic study of the polymorphism of the integrin alpha-2 (platelet glycoprotein Ia/IIa) (ITGA2) gene in pregnant women with fetal growth restriction syndrome.
Keywords: fetal growth restriction syndrome; endothelial system gene; ITGA2 gene